ANÁLISE DA QUALIDADE DE VIDA PRÉ INTERVENÇÃO E A PERCEPÇÃO DE DOR EM PACIENTES PORTADORES DE DOENÇA VENOSA CRÔNICA APÓS A INTERVENÇÃO COM EXERCÍCIOS FISICOS - Portes, Elaine Cristina da Costa (2019)
Chronic venous disease (CVD) is defined as an abnormal functioning of the venous system. Generating venous hypertension, which, later on, causes the skin changes characteristic of the disease. Venous hypertension can affect the superficial, deep or both. The negative effect of CVD is directly linked to the impairment of quality of life (QOL) of its affected, which, in turn, may report pain, tiredness in the legs, tingling, numbness, edema and ulcerations in the advanced stage of the disease. Physical exercise is considered an effective measure of prevention and treatment of CVD. The practice of physical exercise promotes the individual improvement of muscle strength of lower limbs, reduction of edema and improvement of quality of life of individuals with chronic venous disease. Given the above, the objective of this research was to relate physical exercise with the perception of pain improvement and quality of life in patients with chronic venous disease. The sample consisted of 50 adult individuals, of both sexes, aged between 35 and 75 years old. The McGill Pain questionnaire was applied to measure pain intensity and pattern. The WHOQOL-bref questionnaire was also applied to assess the quality of life of individuals. Regarding the analysis, the sample calculation was initially performed using the 95% confidence level. Pearson's correlation was used in the association of physical exercise and pain. The significance level was set at p <0.05. Among the participants, 26% males had significant improvements after exercise intervention on pain intensity variables 2.08 ± 0.64 and pain pattern variables 2.00 ± 0.57, and 74% females, pain intensity 2.03 ± 0.68 and pain pattern 1.86 ± 0.63. Total quality of life and the four domains (physical, psychological, social relations and environment) were classified as unsatisfactory. The data obtained in this study suggest that exercise improves pain intensity and pain pattern in patients with chronic venous disease, and despite the improvement in pain patterns and intensity, quality of life was below satisfactory.